Bilateral Exudative Retinal Detachment Due to Hypertensive Retinopathy and Choroidopathy In Young Patient with Chronic Kidney Disease - Kartikasari, Indha Dwi; Dewi, Nadia Artha; Metita, Mirza; Refa, Safaruddin (International Journal of Retina, 2018)
Introduction: Severe systemic hypertension in chronic kidney disease can cause significant damage to the eye. Although hypertensive retinopathy is a well-known complication, hypertensive optic neuropathy and choroidopathy are much less common. The aim of this study is to report retinal manifestation in young patient with chronic kidney disease. Method: A 26-year-old man with underlying disease chronic kidney disease (CKD) gr-V underwent bilateral bullous exudative retinal detachments. Retinal arteriolar narrowing, vascular tortuosity, arteriovenous nicking, optic disc swelling, retinal haemorrhage, elschnig spot, siegrist streak were identified in both eyes. Blood pressure was 200/140mmHg with visual acuity 0,5/60 OU. The patient was diagnosed with bilateral hypertensive retinopathy and choroidopathy with bulous exudative retinal detachments. Results: After antihypertensive treatment, visual acuity improved, but the exudative retinal detachments and retinal hemorrhages reduced. A patient with those findings should be considered as having hypertensive retinopathy and choroidopathy and treated as soon as possible because of the poor prognostic. Conclusion: Hypertensive choroidopathy is a rare finding associated with acute increases in blood pressure. When the choroid is associated, the hypertensive event is often more acute and associated with increased morbidity. It is necessary to obtain fundus exam in any patient with elevated blood pressure and concomitant vision complaints. Therefore, screening hypertensive patients involves close collaboration between internist and ophthalmologist.